Sociodemographic characteristics and diabetes predict invalid self-reported non-smoking in a population-based study of U.S. adults - Shelton Brent J; Taylor George W; Fisher Monica A; Debanne Sara M (BMC, 2007)
Abstract Background Nearly all studies reporting smoking status collect self-reported data. The objective of this study was to assess sociodemographic characteristics and selected, common smoking-related diseases as predictors of invalid reporting of non-smoking. Valid self-reported smoking may be related to the degree to which smoking is a behavior that is not tolerated by the smoker's social group. Methods True smoking was defined as having serum cotinine of 15+ng/ml. 1483 "true" smokers 45+ years of age with self-reported smoking and serum cotinine data from the Mobile Examination Center were identified in the third National Health and Nutrition Examination Survey. Invalid non-smoking was defined as "true" smokers self-reporting non-smoking. To assess predictors of invalid self-reported non-smoking, odds ratios (OR) and 95% confidence intervals (CI) were calculated for age, race/ethnicity-gender categories, education, income, diabetes, hypertension, and myocardial infarction. Multiple logistic regression modeling took into account the complex survey design and sample weights. Results Among smokers with diabetes, invalid non-smoking status was 15%, ranging from 0% for Mexican-American (MA) males to 22%-25% for Non-Hispanic White (NHW) males and Non-Hispanic Black (NHB) females. Among smokers without diabetes, invalid non-smoking status was 5%, ranging from 3% for MA females to 10% for NHB females. After simultaneously taking into account diabetes, education, race/ethnicity and gender, smokers with diabetes (ORAdj = 3.15; 95% CI: 1.35-7.34), who did not graduate from high school (ORAdj = 2.05; 95% CI: 1.30-3.22) and who were NHB females (ORAdj = 5.12; 95% CI: 1.41-18.58) were more likely to self-report as non-smokers than smokers without diabetes, who were high school graduates, and MA females, respectively. Having a history of myocardial infarction or hypertension did not predict invalid reporting of non-smoking. Conclusion Validity of self-reported non-smoking may be related to the relatively slowly progressing chronic nature of diabetes, in contrast with the acute event of myocardial infarction which could be considered a more serious, major life changing event. These data also raise questions regarding the possible role of societal desirability in the validity of self-reported non-smoking, especially among smokers with diabetes, who did not graduate from high school, and who were NHB females.